(untitled) (Филолошке студије, 2019)
The article examines one of the most interesting mythologisms of the revolutionary and post-revolutionary times, namely – the invisible city of Kitezh. The author reveals as to how the legend about the city of Kitezh is manifested in the poetry of the early 20th century and draws the conception of those literary pieces as paradoxical correlation of the alive and the dead, the real and the unreal, the present and the past.